The Influence of Family Motivation, Knowledge of Profit Sharing Ratio, and Level of Faith on Interest in Working in Islamic Financial Institutions - Ari Sarwo, Ari Sarwo; Sri Rahayu Indah Azhary; Indah Safitri (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
Islam in Indonesia is the majority religion, where the economy is very diverse and plural. This is because Indonesia is dominated by Islamic financial institutions, all societal norms refer to Islamic values, especially the value of muamalah. The Financial Services Authority in Indonesia has provided a report on the development of Indonesian sharia finance as a form of responsibility to encourage the development of a sharia-based financial industry through the compilation of complete and detailed information about the progress of how the Islamic financial industry and the factors that can influence it every year. This study explores the impact of the influence of family motivation, knowledge, profit-sharing ratio and level of faith on career interests in Islamic institutions. The sample used is students of the faculty of economics, the type of research used is quantitative research using primary data types. The results of this study are: family motivation affects work interest, while knowledge of profit sharing ratio and level of faith does not affect student work interest. The next suggestion for researchers is to add samples and focus more on students concentrating on Islamic accounting.